2022
DOI: 10.3389/fonc.2022.883318
|View full text |Cite
|
Sign up to set email alerts
|

NAMPT Inhibition Induces Neuroblastoma Cell Death and Blocks Tumor Growth

Abstract: High-risk neuroblastoma (NB) portends very poor prognoses in children. Targeting tumor metabolism has emerged as a novel therapeutic strategy. High levels of nicotinamide-adenine-dinucleotide (NAD+) are required for rapid cell proliferation. Nicotinamide phosphoribosyl transferase (NAMPT) is the rate-limiting enzyme for NAD+ salvage and is overexpressed in several cancers. Here, we determine the potential of NAMPT as a therapeutic target for NB treatment. NAMPT inhibition cytotoxicity was determined by trypan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…NAMPT upregulation has been reported to be associated with the phosphorylation of AKT ( 48 ). NAMPT inhibition suppressed N-MYC expression and reduced the phosphorylation levels of AKT and GSK3 ( 49 ). Similarly, NAMPTi decreased the dephosphorylation rate of the EGFR, ERK1/2, MEK1/2, and Akt in NSCLC ( 50 ).…”
Section: Nad + Anabolism Dysregulation and Targete...mentioning
confidence: 99%
“…NAMPT upregulation has been reported to be associated with the phosphorylation of AKT ( 48 ). NAMPT inhibition suppressed N-MYC expression and reduced the phosphorylation levels of AKT and GSK3 ( 49 ). Similarly, NAMPTi decreased the dephosphorylation rate of the EGFR, ERK1/2, MEK1/2, and Akt in NSCLC ( 50 ).…”
Section: Nad + Anabolism Dysregulation and Targete...mentioning
confidence: 99%
“…Cancer cells constantly reprogram their metabolism to support the high proliferation rates, such as the Warburg effect of aerobic glycolysis [12][13][14], a critical metabolic hallmark in cancer. NAD+ levels and the NAD+/NADH (nicotinamide adenine dinucleotide) ratio are much higher in cancer cells than in normal cells, suggesting the vital role of NAD+ in cancer cell metabolism [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that NAD+ can strongly induce highly proinflammatory senescence-associated secretory phenotype (SASP) and accelerate cancer progression [10]. Several studies have shown that targeting NAD+ synthesis induces cancer cell cytotoxicity upon NAMPT inhibitor in vitro and in vivo [11,[13][14][15][16][17]. Although previous clinical trials of NAD+ inhibitors showed no effect on remission of advanced solid tumor [18][19][20][21][22], NAD+ is still an intriguing target for cancer therapy and a better understanding of its role in cancer may show some clinical success.…”
Section: Introductionmentioning
confidence: 99%